Applying TOC thinking process tools in managing challenges of supply chain finance: a case study. (1st January 2013) - Mateen, Arqum; More, Dileep
The purpose of this paper is to examine the different challenges that confront supply chain finance (SCF) in Indian business environment, identify the core challenge and develop a concrete action plan to overcome it in an Indian organisation. An exclusive survey was carried out amongst Indian firms to ascertain the perceptions and experiences related to different SCF challenges. To identify the key challenge and prepare a road map to overcome it in an organisation, the five thinking process (TP) tools of the theory of constraints (TOC) were employed. The TP tools helped the organisation in the early stage of implementing SCF initiatives that guided the SCF manager before executing them. This paper is one of the first studies to address and analyse a survey on various challenges confronting SCF and present an integrated application of TP tools in solving a problem of SCF.